2020
DOI: 10.1002/jcc.26475
|View full text |Cite
|
Sign up to set email alerts
|

Comment on “Exploring nature and predicting strength of hydrogen bonds: A correlation analysis between atoms‐in‐molecules descriptors, binding energies, and energy components of symmetry‐adapted perturbation theory”

Abstract: We evaluate the correlation between binding energy (BE) and electron density ρ(r) at the bond critical point for 28 neutral hydrogen bonds, recently reported by Emamian and co-workers (J. Comput. Chem., 2019, 40, 2868). As an efficient tool, we use local stretching force constant k a HB derived from the local vibrational mode theory of Konkoli and Cremer. We compare the physical nature of BE versus k a HB , and provide an important explanation for cases with significant deviation in the BE-k a HB relation as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…There existed a blue region between hydroxyl group and carbonyl group, which was the hydrogen bonding. The binding energy of hydrogen bond was around −50 kJ/mol and it can be classified as the medium‐strength hydrogen bond according to Emamian et al's research 42 . With the link of hydrogen bond, a steady hexatomic ring formed and the red region appeared in the center of hexatomic ring, which was the symbol of the steric effect of ring.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…There existed a blue region between hydroxyl group and carbonyl group, which was the hydrogen bonding. The binding energy of hydrogen bond was around −50 kJ/mol and it can be classified as the medium‐strength hydrogen bond according to Emamian et al's research 42 . With the link of hydrogen bond, a steady hexatomic ring formed and the red region appeared in the center of hexatomic ring, which was the symbol of the steric effect of ring.…”
Section: Resultsmentioning
confidence: 98%
“…The binding energy of intramolecular hydrogen bond was calculated by the method proposed by Emamian et al 42 The wavefunction was regenerated at B3LYP 43 ‐D3(BJ)/ma‐TZVPP 44,45 level, which was consistent with Emamian et al 42 Then, the bond critical point (BCP) 46 of hydrogen bond was searched and its electron density ρ (BCP) was calculated. At last, the binding energy E (HB) can be estimated by Equation () since there was a good linear relationship between them. EHB=932.47×ρBCP+3.1028. …”
Section: Computational Detailsmentioning
confidence: 89%
See 1 more Smart Citation
“…The local mode force constants k a have proven to be a reliable tool to quantify the strength of covalent chemical bonds and weak chemical interactions such as halogen bonds, chalcogen bonds, pnicogen bonds, , tetrel bonds, and hydrogen bonds. A more in-depth discussion of the underlying theory of LMA can be found in refs and and the literature cited therein. LMA was performed with the LModeA software package. , LMA was complemented in this work with the NBO analysis , performed at all identified intermediates and TSs.…”
Section: Methodsmentioning
confidence: 99%
“…Some previous reports have demonstrated that the inter-molecular hydrogen bonds of water result in the illogically high freezing point, significantly diverging from the law of chalcogen hydrides, which indicates that destructing the inter-molecular hydrogen bonds would reduce the melting point of water in thermodynamics. [21,22] In addition, the hydrogen bonds contribute to the formation of ice nuclear. [23] Therefore, the weakened OH bonds denote reduction of glass transformation.…”
Section: Raman Spectramentioning
confidence: 99%